Labour relations under duress in Europe: Contributions for social resilience theory - Calado, A. (2023)
Using a theoretical approach founded on resilience studies, this article presents a comparative analysis of the reconfiguration of labour relations in Portugal, Poland and Ireland during the financial crisis. It proposes a critical understanding of social resilience that captures not only the organisation of the system that emerges post-crisis but also its underlying dynamic power relations, the rule and institutional arrangement systems as well as the redistribution of resources. Moreover, it argues that the crisis created an opportunity for the convergence and liberalisation of labour market models across Europe.